From "intrusive" and "excessive" to financially abusive? Charitable and religious fund-raising amongst vulnerable older people. Issue 2 (11th April 2016) - Redmond, Mark
Abstract : Purpose: – The purpose of this paper is to explore the nature of both charitable and religious fundraising amongst vulnerable older adults. It is a practice that is hidden and opaque. The circumstances surrounding the death of Olive Clarke in spring 2015, however, suggest that it is a practice that involves "intrusive" and "excessive" practices. Fundraising amongst vulnerable older adults is largely unregulated and independently monitored. This paper argues that ensuring the protection of vulnerable older adults requires substantial change and new accountabilities. Design/methodology/approach: – This paper explores current approaches to financial abuse and the focus on family and professional carers as the main likely perpetrators. However, using literature from both the USA and Australia, it considers notions of "trust" and professional behaviour, and the way that vulnerable older adults are subject to new forms of abuse as a result of financial technology such as online and telephone banking. It links this with the practices of charitable fundraisers using techniques such as cold calling and direct mail. Findings: – The circumstances surrounding the death of Olive Clarke suggest that charities, and those fundraise for charities appear to engage in a practice whereby they sell the names of likely donors to each other. This practice opens opportunities for abusive relationships to take place. At the same time many clergy operate like the single GP surgeries that allowed Shipman to practice unnoticed and unaccountable. The relationship between clergy and their aging congregation, who are relied upon to raise funds for church activities, open up the opportunity for abuse to take to place. Few records on charitable giving exist that permit regulation and independent scrutiny. Research limitations/implications: – Current research in this area is limited by the focus on family and professional carers as likely perpetrators of financial abuse, and through attention on child sexual abuse in general. There is a lack of research on charitable giving, and the focus tends to be on altruism rather than the practices and motivations of fundraisers themselves. This paper intends to begin an academic debate to the context in which Olive Clarke took her own life. Practical implications: – In the wake of the death of Olive Clarke the Fundraising Standards Board has been tasked with reviewing the way charities raise funds amongst vulnerable older adults. No one has yet used the language of financial abuse, choosing to opt for the terms "excessive" and "intrusive" there is a need to shift this debate and encourage greater regulation and accountability. Social implications: – This paper seeks to explore how some of the organisations that are supposed to protect and care for vulnerable people engage in practices that exploit and abuse. It is timely as debates about charitable giving are beginning to increase, and the role of the church and the religious groups in the abuse of children is being considered by the new independent inquiry in the UK. It has significant implications for accountability, trust and regulation. Originality/value: – The financial abuse of older adults is rarely considered outside of the family – carer nexus. However, changes in the banking and financial systems means that opportunities for abuse are greater than ever before. Prior to the death of Olive Clarke in spring 2015 very little attention on the nature of charitable and religious fundraising amongst older adults has taken place, and consequently this paper is highly original, but equally timely.